(untitled) (Research, Society and Development, 2021)
An unknown pneumonia-like disease has emerged in Wuhan, China, in late 2019. It is later named as SARS-CoV-2 which cause COVID-19. This virus spreads easily due to high mobilization and its transmission through droplets or aerosol and fomite. The World Health Organization (WHO) then declared this disease as a global outbreak in March 2020. As the world faces the outbreak of SARS-CoV-2, many researchers race to find the most efficacious treatment for COVID-19. Until now, the most common treatments for COVID-19 were only symptomatic such as decongestant, corticosteroid, interleukin inhibitor, and existing antiviral. The researchers then develop a brand new antiviral that works efficiently to inhibit SARS-CoV-2 and might become prophylaxis. This disease is called Molnupiravir or EIDD-2801, a nucleotide analog which inhibits SARS-CoV-2 replication, resulting in damaged mRNA and lethal virions. Molnupiravir works to produce mutagenesis in RNA viruses and prevent the virus from spreading widely throughout the human body. However, this drug is still needed to undergo clinical trial phase three. In this article, we will discuss how Molnupiravir works and its efficacy compared to existing drugs. This review article aims to provide an update about novel efficacious antiviral for COVID-19, Molnupiravir.